2016
DOI: 10.1590/s0080-623420160000700018
|View full text |Cite
|
Sign up to set email alerts
|

Fall and its association with the frailty syndrome in the elderly: systematic review with meta-analysis

Abstract: Objective:To analyze the prevalence of falls and frailty syndrome and the association between these two syndromes in the elderly population. Method: Systematic review, without restriction of dates, in English, Portuguese and Spanish languages, in the databases PubMed, CINAHL, LILACS and in the SciElo virtual library. The association between both variables was extracted from the studies (Odds Ratio and 95% Confidence Intervals). Results: The review included 19 studies published between 2001 and 2015. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 45 publications
4
48
1
18
Order By: Relevance
“…As for time of occurrence, there was a greater number of falls in the daytime period, which agrees with a study that presented similar results, inferring that this occurs due to the fact thatthe day corresponds to the period in which the elderly develop their activities of daily living, in relation to the night period [13,14].…”
supporting
confidence: 90%
“…As for time of occurrence, there was a greater number of falls in the daytime period, which agrees with a study that presented similar results, inferring that this occurs due to the fact thatthe day corresponds to the period in which the elderly develop their activities of daily living, in relation to the night period [13,14].…”
supporting
confidence: 90%
“…Frailty has been established to be a risk factor for falls (Kojima, 2015). Several systematic reviews have also suggested a possible association between falls and prefrailty (Cheng & Chang, 2017;Fhon, Rodrigues, Neira, Huayta, & Robazzi, 2016;Kojima, 2015). Because prefrailty is prevalent in older people (Kojima et al, 2017), the impact on older people would be rather large and intervention to prevent falls in prefrail older people would be warranted.…”
mentioning
confidence: 99%
“…Most studies find association between frailty and falls [ 1 , 11 , 15 , 25 , 26 ], although the relationship is unclear at the less-pronounced stages of frailty, reflecting the complexity in defining the transition from robust to pre-frail and frail. The strength of the association also varies depending on the age ranges, sex and setting of the studied populations [ 6 ].…”
Section: Discussionmentioning
confidence: 99%